2020–2021 Vegetable Production Handbook: Chapter 11. Legume Production - Peter J. Dittmar; Eugene J. McAvoy; Dakshina R. Seal; Shouan Zhang; Josh H. Freeman; Johan Desaeger; Qingren Wang (EDIS)
This chapter covers production of legumes, such as peas and beans.